“Father against Mother” or the Anti-Liberalism - Couto, Elvis (A Cor das Letras, 2026)
This paper analyzes the discourse of the short story “Father against Mother”, published by Machado de Assis in 1906 in the volume Relíquias de casa velha, with the aim of verifying, based on notions of dialectical criticism from Goldmann and Candido, the homology that exists between the narrative structure and the historical-political structure of Rio de Janeiro society in the 19th century. Thus, we discuss the incompatibility between liberal principles and practices common to the Ancien Régime, such as direct personal domination—the favor mechanism—and slavery. Finally, we seek to grasp possible ideological meanings underlying the narrator's perspective: on the one hand, paternalism as a solution less harmful to slaves than the false abolitionism of liberal republicans; on the other hand, skepticism towards a bourgeois-democratic arrangement.